REGRESI KUADRAT TERKECIL PARSIAL MULTI RESPON UNTUK STATISTICAL DOWNSCALING (Multi Response Partial Least Square for Statistical Downscaling) - Aji Hamim Wigena (FORUM STATISTIKA DAN KOMPUTASI, 2011)
In  climatology  partial  least  square  regression  (PLSR)  can  be  used  as  an alternative  technique  in  statistical  downscaling  based  on  global  circulation model  (GCM)  output.  PLSR  is  the  technique  to  forecast  not  only  one  response but  also  multi  responses  to  accommodate  the  correlation  among  responses. PLSR is compared to PCR (Principal Component Regression). The results show that PLSR is better than PCR and can be used to forecast rainfall simultaneously in more than one rainfall stations relatively as well as in one station.  Keywords: statistical downscaling, PLSR, PCR, multi responses